Risk of Myopathy in Patients in Therapy with Statins: Identification of Biological Markers in a Pilot Study - Camerino, Giulia M.; Musumeci, Olimpia; Conte, Elena; Musaraj, Kejla; Fonzino, Adriano; Barca, Emanuele; Marino, Marco; Rodolico, Carmelo; Tricarico, Domenico; Camerino, Claudia; Carratù, Maria R.; Desaphy, Jean-François; et al. (Frontiers in Pharmacology, 2017)
Statin therapy may induce skeletal muscle damage ranging from myalgia to severe rhabdomyolysis. Our previous preclinical studies showed that statin treatment in rats involves the reduction of skeletal muscle ClC-1 chloride channel expression and related chloride conductance (gCl). An increase of the activity of protein kinase C theta (PKCtheta) isoform, able to inactivate ClC-1, may contribute to destabilize sarcolemma excitability. These effects can be detrimental for muscle function leading to drug-induced myopathy. Our goal is to study the causes of statin-induced muscle side effects in patients at the aim to identify biological markers useful to prevent and counteract statin-induced muscle damage. We examined 10 patients, who experienced myalgia and hyper-CK-emia after starting statin therapy compared to 9 non-myopathic subjects not using lipid-lowering drugs. Western Blot (WB) analysis showed a 40% reduction of ClC-1 protein and increased expression of phosphorylated PKC in muscle biopsies of statin-treated patients with respect to untreated subjects, independently from their age and statin type. Real-time PCR analysis showed that despite reduction of the protein, the ClC-1 mRNA was not significantly changed, suggesting post-transcriptional modification. The mRNA expression of a series of genes was also evaluated. MuRF-1 was increased in accord with muscle atrophy, MEF-2, calcineurin (CN) and GLUT-4 transporter were reduced, suggesting altered transcription, alteration of glucose homeostasis and energy deficit. Accordingly, the phosphorylated form of AMPK, measured by WB, was increased, suggesting cytoprotective process activation. In parallel, mRNA expression of Notch-1, involved in muscle cell proliferation, was highly expressed in statin-treated patients, indicating active regeneration. Also, PGC-1-alpha and isocitrate-dehydrogenase increased expression together with increased activity of mitochondrial citrate-synthase, measured by spectrophotometric assay, suggests mitochondrial biogenesis. Thus, the reduction of ClC-1 protein and consequent sarcolemma hyperexcitability together with energy deficiency appear to be among the most important alterations to be associated with statin-related risk of myopathy in humans. Thus, it may be important to avoid statin treatment in pathologies characterized by energy deficit and chloride channel malfunction. This study validates the measure of ClC-1 expression as a reliable clinical test for assessing statin-dependent risk of myopathy.